Validity of Booklet on Pattern of Inheritance in the Law of the Minister as a Genetic Learning Suplement in High School - Neli Octiana; Syamsurizal Syamsurizal; Rahmawati Darussyamsu; Relsas Yogica (Universitas Negeri Padang, 2020)
The learning process is an interaction between teachers and students in transferring and interpreting experiences and knowledge they have in a new format. The process of transfer and interpretation of biology learning runs optimally supported by learning supplements. Learning media consists of LKS (student worksheet) and printed books based on Curriculum 2013 are available schools, but learning suplements are still rarely used in schools. This research is a development research that uses the Plomp model which consists of initial investigation phase (preliminary research), development of protitpe phase (development or prototyping phase), and assessment phase. Data are analyzed qualitatively and quantitatively. In the booklet development phase validated by 3 evaluators. In assesment booklets phase a practical test was conducted by 1 teacher and 30 students of the XII Adabiah Padang class. From the results of expert review (validation), the validity value of 93.13% was obtained with very valid criteria. The results of the practicality test by the teacher show that the booklet has a value of 93.06% practicality and 93.80% by students with very practical criteria. The booklet developed has very valid criteria and is very practical.